Rock physics characterization of Conway granite from a DOE borehole, Conway, New Hampshire - Warren, N. (Los Alamos Scientific Laboratory, 1979)
The Conway granite of New Hampshire is a highly radioactive intrusive into which a 1-km-deep borehole was drilled and continuously cored in 1975. There are two major granitic units, the Osceola and the Conway. The Conway is cut by three lamprophyre dikes. Elastic moduli and petrographic studies were on 14 samples from the core. These data and observations have been used to determine groupings in the rocks by characterizing microstructure. An important result is that carefully taken physical properties data (for example, velocities and strains) are sensitive indicators of microstructure. Based on velocity and strain data, three distinct groups are found: the lamprophyre dike rocks and two groups each of which contain samples from both the Osceola and Conway formations. These groups are also distinguished by petrographic observations of microcrack patterns. The groups are apparently controlled by grain size and by uniformity of the mixing of the mineral phases in the samples, and not by mineral modes or depth. This last result implies the coring of the Conway samples may have intensified the amount of cracking over that in the rocks in situ, but not the type of cracking. Coring does not apparently induce a distinct population of very thin (low aspect ratio) cracks; that is, such cracks are not needed to explain the low pressure stress and velocity data of these samples.